2014
DOI: 10.4314/tjpr.v13i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Aqueous Extract of <i>Sempervivum tectorum</i> L (<i>Crassulaceae</i>) on Aluminium-Induced Oxidative Stress in Rat Blood

Abstract: (CAT, 49.59 %, p < 0.001), glutathione (GSH, 13.49 %, p < 0.001) and glutathione reductase 23.08 %, p < 0.0001)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Sempervivum tectorum L., an evergreen plant, known as the common houseleek, is a perennial herb with a dense basal rosette of fleshy sharp-tipped, obovate to oblong leaves having red-colored flowers arranged in terminal cymes [17][18][19]. The houseleek is a drought-resistant plant, native to central and southern Europe, growing on roofs, scree, and weathered rocks, traditionally used fresh rather than dried [18,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sempervivum tectorum L., an evergreen plant, known as the common houseleek, is a perennial herb with a dense basal rosette of fleshy sharp-tipped, obovate to oblong leaves having red-colored flowers arranged in terminal cymes [17][18][19]. The houseleek is a drought-resistant plant, native to central and southern Europe, growing on roofs, scree, and weathered rocks, traditionally used fresh rather than dried [18,20].…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum-induced oxidative stress is considered a major cause of male reproductive disorders [7][8][9][10][11]. S. tectorum has been reported to exhibit significant antioxidant activity due to its phytochemical constituents [21]; the antioxidative capacity of S. tectorum can help mitigate the oxidative damage caused by aluminum exposure and protect against reproductive disorders [17].…”
Section: Introductionmentioning
confidence: 99%
“…Its liver-protecting and membrane-stabilizing effects, which have been attributed to antioxidant activity, have been described [22,23]. M. Florin et al described the protective effects of aqueous extract of S. tectorum on aluminum-induced oxidative stress in rat blood, indicating its good antioxidant properties [24]. Some articles have shown that leaf juice from S. tectorum contains polyphenol compositions [16] and high flavonoid content [25].…”
Section: Introductionmentioning
confidence: 99%
“…Chromatographically purified fractions of S. tectorum L. in which rare natural components have been identified-monosaccharide sedoheptulose and polyalcohol 2-C-methyl-D-erythritol, as well as known organic acids and flavonoids, demonstrate the therapeutic effects of the plant in the healing of wounds [15]. Sempervivum tectorum extracts have been used to normalize oxidative stress biomarkers in the blood of rats [16].…”
Section: Introductionmentioning
confidence: 99%
“…Although several pharmacological properties have been reported for the leaves of Sempervivum tectorum L., a complete characterization of the extracts is not yet available. Therefore, only the polyphenolic contents and, in part, the antioxidant activities have been studied [16,18].…”
Section: Introductionmentioning
confidence: 99%